Confronting Gender Violence through Hokmah Education: A Dialogue with Arendt’s Banality of Evil and Proverbs 1 - Park, Hye Kyung (Scriptura Indonesia, 2025)
This research project aims to analyze Proverbs 1 through the lens of Hannah Arendt’s theory of the banality of evil, as articulated in her report on the trial of Adolf Eichmann, in order to contribute to the prevention of gender-based violence. Arendt’s account of the trial emphasized Eichmann’s failure to exercise three essential virtues in his official duties: thinking, judging, and acting. Similarly, this study argues that contemporary gender discrimination and violence often arise from a desire that perpetrators seek to gratify incrementally and insidiously. In incidents of gender - based violence, the perpetrators’ intentions and actions — characterized by moral negligence and a lack of reflection — can be examined through the framework of the banality of evil. This paper also engages with two ancient Chinese philosophers, Mencius and Xunzi, to explore understandings of moral action in human life and to compare their perspectives with Arendt’s. Mencius held that “human nature is good,” whereas Xunzi proposed the “theory of natural evilness.” However, these classical views on human nature fall short in analyzing the moral dimensions of gender - based violence, particularly as such violence is closely tied to the gratification of sexual desire. As Arendt demonstrates through Eichmann’s case, evil often manifests not as monstrous intent but as thoughtlessness. In a similar way, sexual offenses occur in the absence of reflective thought by perpetrators, whose senseless actions bring suffering to their victims. Although their desires ought to be restrained, it is their failure to think and judge ethically that enables such gendered violence to occur. This research proposes hokmah (wisdom) education, as described in Proverbs 1 within Christian wisdom literature, as a foundation for promoting gender awareness in higher education. Hokmah education offers a paradigm shift in gender studies by highlighting the suppression of violent or destructive desires from a feminist perspective. This study also emphasizes the dialogue between Arendt’s political philosophy and biblical texts, employing interdisciplinary methods. Through processes of thinking, judging, and acting grounded in religious reflection, human beings are guided to wisely submit to the divine — who consistently upholds justice as a means of preventing gender-based violence. Arendt’s theory of the banality of evil will be explored throughout the research process. This study will apply her concept to contemporary violence against women and examine its relevance in the context of hokmah education.